THE ROLE OF ULTRASOUND EXAMINATION IN THE DIAGNOSIS OF ATOPIC DERMATITIS IN CHILDREN - Abidov Kh.A., Utkirova Sh.M., (Central Asian Journal of Medicine, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin condition characterized by impaired skin barrier function, immune dysregulation, and vascular changes, posing significant diagnostic and monitoring challenges. Recent advancements in high-frequency ultrasound imaging, Doppler ultrasonography, and shear-wave elastography have positioned ultrasound as a promising non-invasive tool for assessing structural and functional skin changes in AD. This article reviews the diagnostic value of ultrasound in evaluating epidermal and dermal alterations, vascularization, and tissue elasticity in pediatric AD patients. By analyzing data from clinical studies, we highlight how ultrasound complements traditional diagnostic methods, such as the SCORAD index, and supports personalized treatment strategies. The integration of ultrasound modalities enhances the understanding of AD pathogenesis and aids in monitoring disease progression and therapeutic efficacy.